Bovine Leukemia Virus Infection in Neonatal Calves. Risk Factors and Control Measures - Ruiz, Vanesa; Porta, Natalia Gabriela; Lomónaco, Marina; Trono, Karina; Alvarez, Irene (Frontiers in Veterinary Science, 2018)
Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leukosis (EBL). Although efficient eradication programs have been successfully implemented in most European countries and Oceania, BLV infection rates are still high worldwide. BLV naturally infects cattle, inducing a persistent infection with diverse clinical outcomes. The virus infects lymphocytes and integrates a DNA intermediate as a provirus into the genome of the cells. Therefore, exposure to biological fluids contaminated with infected lymphocytes potentially spreads the virus. Vertical transmission may occur in utero or during delivery, and about 10% of calves born to BLV-infected dams are already infected at birth. Most frequently, transmission from dams to their offspring occurs through the ingestion of infected colostrum or milk. Therefore, although EBL is not a disease specific to the neonatal period, during this period the calves are at special risk of becoming infected, especially in dairy farms, where they ingest colostrum and/or raw milk either naturally or artificially. Calves infected during the first week of life could play an active role in early propagation of BLV to susceptible animals. This review discusses the main factors that contribute to neonatal BLV infection in dairy herds, as well as different approaches and management practices that could be implemented to reduce the risk of BLV transmission during this period, aiming to decrease BLV infection in dairy herds.